The Electric Supply Chain 4.0 - Zomkowksi Salvi, Vinícius (Archives of Business Research, 2020)
Supply Chain Management is not a Discipline, but it is becoming one. Supply Chain as Network is a modern definition of a field with more than 37 years of reliable scientific publications. And it has great complexity even greater when world is experiencing the Forth Industrial Revolution. Electricity Supply Chains were delimitated as those compounded by first tier of oil, gas or coal (energy production majority), the generators, the transmitters, the distributor retailer until end-consumer. It has a great complex network constituted by external organisms responsible for coordinating and giving the strategy to the whole system. Lean and Agile is something less usual in Electricity Supply Chain. This researcher was unable of finding scientific articles reporting directly about that combination. However, Electricity Supply Chain is considered a functional product with long life cycle. The coal, the gas and the oil are also functional products and they are controlled with efficient perspective. It is concluded that Electricity supply chain is more designed for a lean environment to an agile positioning. The industry 4.0 is transformed the whole Electricity Supply Chain, especially the electric utility. It is using Big Data for generating extra businesses, and for improving operational conditions. The smart meter and the smart grid, using sensors and the Big Data, coordinate a more precise cycle of production and consumption, transforming Electricity Supply Chain into a responsiveness one with real date and virtual networks.